2008
DOI: 10.1007/s10765-008-0386-0
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Microstructures: Modification and Characterization by Fluid Sorption

Abstract: Polymer micro-organization can be modified by a combination of three constraints, thermal, hydrostatic, and fluid sorption. In selecting the fluid's nature, chemically active or inert, and its physical state, liquid or supercritical, new "materials" can be generated. In addition, the interplay of temperature and pressure allows tailoring the obtained material structure for specific applications. Several complementary techniques have been developed to modify, analyze, and characterize the end products: scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…For cyclohexane, the conversion of the crystallization thermogram of the confined liquid into pore size distributions was performed using the equations published in a previous work. 24 A specific program was used for the thermoporosimetry experiment with a drying step which allows observation of the progressive desorption of the confined solvent and thus estimation of the size of the un-swelled mesh. Successive cooling programs were performed including drying periods between each cooling.…”
Section: Thermoporosimetrymentioning
confidence: 99%
“…For cyclohexane, the conversion of the crystallization thermogram of the confined liquid into pore size distributions was performed using the equations published in a previous work. 24 A specific program was used for the thermoporosimetry experiment with a drying step which allows observation of the progressive desorption of the confined solvent and thus estimation of the size of the un-swelled mesh. Successive cooling programs were performed including drying periods between each cooling.…”
Section: Thermoporosimetrymentioning
confidence: 99%
“…Recently, Nedelec et al 17 reported that the coagulation radius estimated by differential scanning calorimetry (DSC) measurements can be described by an exponential function. [15][16][17][18][19] The former relationship corresponds to the first-order Taylor polynomial of the latter one. By using the first-order approximate function, 20,21 we reported the coagulation dimension of water in a PVA hydrogel formed from freeze/thaw cycles.…”
Section: Introductionmentioning
confidence: 99%